Late Paleozoic Climatic Reconstruction of Western Argentina: Glacial Extent and Deglaciation of Southwestern Gondwana - (:unkn) unknown (My University, 2020)
Throughout its history Earth has experienced both icehouse and greenhouse conditions. Shifts and transitions from one end member to the other are driven by numerous driving mechanisms on global, orbital and more local scales. In particular, the late Paleozoic ice age (LPIA) is thought to have been driven by global drivers such as the drift of the Gondwanan continent across the South Pole, fluctuations in atmospheric CO2 concentrations, and Milankovitch cycles. It was also affected by more local and regional drivers such as active tectonism along accretionary margins and changes in atmospheric and oceanic circulation patterns. South American Gondwana provides an excellent opportunity to examine and evaluate the effects that global versus local driving mechanisms had on regional climates during the shift from icehouse to greenhouse conditions around the Carboniferous-Permian boundary. Of particular interest to this study are the margin and foreland basins of western Argentina in comparison to their paleolatitudinal counterparts of Brazil and eastern Argentina (i.e. the Chaco-Paraná and Paraná basins). This study focuses on determining the extent of glaciation during the Serpukhovian-Bashkirian of the Paganzo and Calingasta-Uspallata basins, the subsequent and relatively early deglaciation and shift in climate from humid conditions to extreme aridity, and the driving mechanisms for this change. This study tracks changes in facies, sediment dispersal, and climate indicators throughout the late Paleozoic strata in the Paganzo, Calingasta-Uspallata and Paraná basins, with special focus on the Paganzo Group strata. Here, we conclude that glaciation of the Paganzo and Calingasta-Uspallata basins was restricted to the Precordilleran region and nucleated on a significant uplift known as the Protoprecordillera and adjacent uplands. A paleoclimate reconstruction for the late Carboniferous using the Chemical Index of Alteration (CIA) indicates a shift from cold and arid to warm and humid following the deglaciation of the region, which is then succeeded by a drastic shift to an extremely arid environment. A provenance study using detrital zircon geochronology for selected units of the Paganzo Group strata indicates a restricted foreland basin setting in the early-middle Carboniferous that evolves and broadens through the Pennsylvanian and into the Permian as the active tectonic margin moves westward. With the accretion of a magmatic arc during the latest Carboniferous, the detrital zircon geochronology and the facies of the Paganzo Group record an enhancement, or an increase/expansion of the orographic effect originally created by the Protoprecordilleran range during the early-middle Carboniferous glaciation.
Keywords: Argentina; Gondwana; late Paleozoic ice age; Paganzo Basin; Paleoclimate; Provenance